PELAKSANAAN KODE ETIK APARATUR SIPIL NEGARA DI KANTOR BKPSDM KABUPATEN TANAH DATAR - Ranti Hanafiah; Karjuni Dt Ma'ani (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
The Code of Ethics is a rule that contains behavior that must be obeyed by those who carry out certain professional duties. However, until now there are still found violations of the code of ethics discipline in Tanah Datar District. This study aims to describe the implementation of the Code of Ethics for State Civil Servants at the Office of the Civil Service and Human Resources Development of Tanah Datar Regency, as well as to identify obstacles in the implementation of the Code of Ethics for State Civil Servants at the Office of the Civil Service Agency and Human Resources Development of Tanah Data Regency. This research uses qualitative research using descriptive method which is done by purposive sampling. Data collection techniques were carried out by observation, interviews and documentation study, with sources from several employees at the Office of the Civil Service and Human Resources Development of Tanah Datar Regency and several communities related to the Implementation of the Code of Ethics for State Civil Servants. One of the actions of the Tanah Datar District Civil Service and Human Resources Development Agency against State Civil Servants who commit disciplinary violations is by giving warnings and reductions in accordance with Government Regulation Number 53 of 2010 concerning Civil Servant Discipline.